The dispersal paradox : can lowland granivorous mice also disperse the seeds they devour? - Gwynne-Evans, David (Department of Biological Sciences, 2017)
The relationship between two rodent species and the Cape Reed (Willdenowia incurvata) were examined. Many studies have focussed on the role of rodents as predators of plant seeds. However, it seems that certain rodents may actually perform a crucial role in the dispersal of plants. Experiments to uncover the dispersal mechanism were carried out. Also examined is the role of the appendages present on the Restio seeds, possibly as energy-rich rewards for dispersal for the rodents. It was found that the Restio may be dependent on seed-dispersing rodents, although this mutualism is not so important in fragmented habitats.